Multiband and wideband characteristics of grid array antenna - Yahya, Muhammad Sani; Hamzah, Shipun Anuar; Ramli, Khairun Nidzam; Seman, Fauziahanim Che; Abu, Maisarah; Nordin, Shahilah; Malik, Nik Noordini Nik Abd; Mustapa, Mohammad Sukri (2023)
An inexpensive and non-complex technique for achieving multiband and wide bandwidth on Grid Array Antenna (GAA) is presented in this work. By cutting a square slot on the ground plane of a conventional GAA at a determined distance from the center of the ground plane of a conventional GAA, wide and multiband GAA was achieved. Simulation results indicate that the impedance bandwidth covered by the antenna is from 23.54 GHz - 24.43 GHz, 27.81 GHz - 30.80 GHz and 32.67 GHz - 40.19 GHz with a gain of 15.44 dBi at 37 GHz. The bands covered by the antenna are essential for 5G millimeter-wave communications.